Endometriosis is a disease of immune dysfunction, which could be linked to microbiota - Liu, Hongyan; Li, Junxia; Guan, Chenchen; Gao, Wenjie; Li, Yan; Wang, Jianmei; Yang, Yang; Du, Yongrui (Frontiers in Genetics, 2024)
Endometriosis, characterized by extrauterine endometrial tissue, leads to irregular bleeding and pelvic pain. Menstrual retrograde theory suggests fragments traverse fallopian tubes, causing inflammation and scar tissue. Prevalent among infertile women, risk factors include fewer pregnancies, delayed childbirth, irregular cycles, and familial predisposition. Treatments, medication, and surgery entail side effects.Studies link gut microbiota alterations to endometriosis, necessitating research to establish causation. We used Mendelian randomization to investigate the potential link between endometriosis and gut microbiota through genetic variants.Two-sample Mendelian randomization analyzed gut microbiota's potential causal effects on endometriosis. Instrumental variables, robustly associated with exposures, leveraged GWAS data from MiBioGen for gut microbiota and FinnGen R8 release for endometriosis. SNPs strongly associated with exposures were instrumental variables.Rigorous assessments ensured SNP impact scrutiny on endometriosis.At the genus level, Anaerotruncus, Desulfovibrio, Haemophilus, and Holdemania showed causal association with endometriosis. Specific gut microbiota exhibited causal effects on different endometriosis stages. Holdemania and Ruminococcaceae UCG002 exerted reversible, stage-specific impacts.Mendelian randomization provides evidence for the causal link between specific gut microbiotas and endometriosis, emphasizing the pivotal role of gut microbiota dysbiosis. Modulating gut microbiota emerges as a promising strategy for preventing and treating endometriosis.